NEOPHOBIA IN INFANTS: HOW TO FORM FOOD PREFERENCES? - I. N. Zakharova; Yu. A. Dmitrieva (Вопросы современной педиатрии)
Many aspects of pediatric dietology have been studied recently. According to them an optimal diet can be developed both for healthy children and children with certain nutritional requirements. However some issues of physiology of nutrition remain unsolved. In particular, the problem of formation of food preferences in infancy is widely discussed in scientific literature. The results of numerous researches suggest existence of certain critical period in infancy, when genetically-based food preferences are influenced by maximal exposure of external factors. The main role among such factors has the first experience of introduction of different tastes to a child during diet widening. This determines special attention of specialists to the problem of introduction of additional baby food and development of appropriate diet since the first months of life. The results of scientific studies clearly demonstrated, that balanced diet in the first years of life, developed according to the physiological requirements, health condition and national traditions, allows not only to provide optimal growth rate of a child, but to overcome the problem of the negative attitude to new food products.